Integration of Small RNA and Transcriptome Sequencing Reveal the Roles of miR395 and ATP Sulfurylase in Developing Seeds of Chinese Kale - Tang, Weiling; Zhao, Yijiao; Zeng, Jiajing; Li, Zunwen; Fu, Zhenlin; Yang, Mengyu; Zeng, Donglin; Chen, Xiaodong; Lai, Zhongxiong; Wang-Pruski, Gefu; Guo, Rongfang (Frontiers in Plant Science, 2022)
Seed development is closely related to plant production and reproduction, and miRNA is widely involved in plant development including seed development. Chinese kale, as a Brassicaceae vegetable, mainly depends on seed for proper reproduction. In the present study, Chinese kale seed and silique at different stages were selected to establish sRNA libraries including PC, PD, SC, and SD. The results showed that miRNA expressed differentially in the seeds and corresponding siliques at different stages. To further clarify the functional mode of miRNA in the process of seed development, KEGG enrichment analysis was performed on target genes of the differentially expressed miRNAs, and these target genes were mainly enriched in plant hormone signal transduction, primary and secondary metabolic pathways. After joint analysis with the transcriptome change of the corresponding period, miR156-SPL10/SPL11, miR395-APS3, and miR397-LAC2/LAC11 modules were identified to be directly involved in the development of Chinese kale seeds. What’s more, modified 5’RLM-RACE and Agrobacteria-mediated Chinese kale transient transformation suggest miR395b_2 is involved in sulfur metabolism during seed development by regulating its target gene APS3.